ANTITHROMBOCYTOPENIA ACTIVITY OF PEANUT SHELL (Arachis hypogea L.) EXTRACT AND INFUSA ON HEPARIN INDUCED BALB/C MICE - risha fillah fithria; Ririn Lispita Wulandari; Devi Nisa Hidayati; Pia Annisa; Nilam Eka Putri (Balai Besar Penelitian dan Pengembangan Tanaman Obat dan Obat Tradisional, 2019)
ABSTRACT Certain group of people empirically use peanut shell stew in the treatment of thrombocytopenia due to dengue fever. The active compounds suspected to play a role in the activity of thrombocytopenia from peanut shell are flavonoids. Flavonoids can be extracted using heat and cold methods. This study aims to determine the antithrombocytopenia activity of peanut shell extract and infusa on heparin induced Balb/C mice. This study is an experimental research with randomized matched pre and postest control group design. Peanut shell extraction was done in a cool way by maseration using 70% ethanol solvent, and hot way by infundation using aquadest solvent. Forty-eight Balb/C mice were divided into 8 groups consisting of control group CMC Na 0.5 mL/20gBW/day, control group aquadest 0,5mL/20gBW/day, 3 groups of peanut shell ethanol extract (0.019, 0.038, and 0.076) g/20gBW/day, and 3 groups of peanut shell infusa (0.026, 0.052; 0.104) g/20gBW/day. All treatments were given orally. The decrease of platelet count in Balb/C mice using 26 UI/20gBW subcutan heparin induction. The measurement of the platelet count is performed by taking blood samples in the lateral veins of the tail. Platelet counts data before and after treatment was tested with dependent T-test. Differences in platelet increases across the groups were tested by 2 way anova and continued with a LSD test with 95% confidence level. The results showed that peanut shell ethanol extract had better antitrombocytopenia activity than peanut shell infusa.